Environmentally-defined enhancer populations regulate diversity of tissue-resident macrophages. Issue 2 (February 2015) - Bulger, Michael; Palis, James
<x xml:space="preserve">Abstract</x> Macrophages represent a class of cells specialized for phagocytosis that occurs in multiple, phenotypically distinct populations throughout the body. Two studies published in Cell demonstrate that these phenotypic differences reflect drastic differences in the populations of enhancers that regulate transcription, and that this epigenomic diversity is, in fact, highly plastic and sensitive to environmental cues.